«Green economy» as priority direction of Kazakhstan development (Eurasian Journal of Ecology, 2016)
Abstract. In this article the author examines the concept of "green economy" as one of the strategic directions of development of Kazakhstan. Explored the concept of the transition of Kazakhstan to the "green economy", its main goals and objectives. Analyzes the main problems of the global ecosystem.
Keywords: «green economy»; ecology; resource management; efficiency; development